Knowledge level and attitude of midwifery and nursing students regarding AIDS, Babol, 2000 - Sh Omidvar (Babol University of Medical Sciences, 2003)
Background and Objective: HIV attacks immune cells and causes impairment of immune system and disorder the defense of body against diseases. Since, 90% of infections occur in developing countries. The aim of this study was to determine the knowledge level and attitude to AIDS among nursing and midwifery students. Methods: This descriptive and analytical study was carried out on 150 nursing and midwifery students (From Azad university and State-Run university) who were in second year and higher level courses. Samples were randomly selected and then their knowledge and attitude was determined by the questionnaire. Also, the relationship between the knowledge level with their field, educational year and university were determined by Chi-square test and the relationship between knowledge and attitude was determined by Pearson correlation coefficients. Findings: The results indicated that all students obtained information on AIDS and most of them obtained information only from media (58%) and none of them was very knowledgeable but the most frequency related to good knowledge level. There was a significant relationship between the knowledge level with university and field (P<0.05). But, there was not a significant relationship between the knowledge level and educational year. None of subjects had a positive attitude to AIDS. No significant relationship was found among the attitude and field, educational year and university. Pearson correlation coefficients indicated a direct relationship between the knowledge level and attitude towards AIDS. Conclusion: According to the results, university education had little effect on knowledge level. Concerning AIDS pandemy, it must be given more information to medical students and suggested to consider this information as a lesson course.